2022
DOI: 10.1186/s12879-022-07115-w
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing patients with rare mucormycosis infections using real-world data

Abstract: Background Invasive mucormycosis (IM) is a rare and often life-threatening fungal infection, for which clinical and epidemiological understanding is lacking. Electronic health record (EHR) data can be utilized to elucidate large populations of patients with IM to address this unmet need. This study aimed to descriptively assess data on patients with IM using the Optum® EHR dataset. Methods US patient data from the Optum® deidentified EHR dataset (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(55 reference statements)
0
0
0
Order By: Relevance
“…Even though the majority of Middle Eastern nations use electronic health records, there are limitations on updating the database to include data on laboratory markers and medication intake in order to maximize IFI management. Recently, the United States implemented Optum®, a data collection strategy, to gather anonymous data on invasive mucormycosis [69]. The Middle East could benefit from the development of these prediction models in order to collect information on the different types of IFIs, including the causative bacteria, AFT used, and patient outcomes.…”
Section: Management Challengesmentioning
confidence: 99%
“…Even though the majority of Middle Eastern nations use electronic health records, there are limitations on updating the database to include data on laboratory markers and medication intake in order to maximize IFI management. Recently, the United States implemented Optum®, a data collection strategy, to gather anonymous data on invasive mucormycosis [69]. The Middle East could benefit from the development of these prediction models in order to collect information on the different types of IFIs, including the causative bacteria, AFT used, and patient outcomes.…”
Section: Management Challengesmentioning
confidence: 99%
“…From 2001 to 2006, the Transplant-Associated Infection Surveillance Network (TRANSNET) in America reported 44 IM (0.3%) of 15,820 HSCT patients [7]. A multicenter, retrospective study conducted in America found that 1133 of 962,428 HMs patients suffered from IM (0.12%) between 2007 and 2019 [8]. From 2007 to 2017, a survey of the Children's Cancer Hospital in Egypt found 45 cases of proven IM among 13,735 hospitalized children (0.33%) who suffered from tumors [9].…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…While electronic health records are used in most Middle Eastern countries, updating the database to include information on laboratory indicators and drug usage to optimize IFI management is limited. Recently, a data acquisition model called Optum® has been implemented in the US to collate unidentified data on invasive mucormycosis [ 46 ]. The development of such prediction models can be useful in the Middle East region to collate data on diverse types of IFIs, including causal pathogens, AFT used, and patient outcomes.…”
Section: Reviewmentioning
confidence: 99%